Synthesis, Structure and Characterization of the Oxo-Bridged Binuclear Nickel(II) Complex [Ni2(C6H4NO2)4]O·1.5H2On - Li, Yumei (Asian Journal of Chemistry, 2010)
The novel coordination polymer with the molecular formula [Ni 2(C6H4NO2)4]O·1.5H2On was obtained by self-assembly and the structure was determined by X-ray crystallography. Two Ni atoms bridged with oxygen atoms form a non-linear complex. The analytical conclusions reveal that nicotinic acid adopts two coordination modes: μ2-nic-N, O and μ3-nic-N, O, O and two octahedral coordinated nickel(II) atoms bridged with oxygen.